GAMBARAN PENGETAHUAN KELUARGA TENTANG PENATALAKSANAAN KEGAWATDARURATAN KRISIS HIPERTENSI DI RUMAH - Agus Murtana; Endang Sawitri; Fatimah Nur Lintang; Puput Risti Kusumaningrum; Marwanti (MOTORIK Jurnal Ilmu Kesehatan, 2025)
Hypertensive crisis is a clinical condition characterized by very high blood pressure that can cause or has caused target organ abnormalities. It is usually characterized by blood pressure >180/120 mmHg. Methods: This type of research is a descriptive study using quantitative methods and a cross sectional approach. The study population was 55 people. The sample was taken with total sampling of 55. This research will be conducted on June 1-30, 2025. The research instrument was a questionnaire: Primary data were obtained from a questionnaire consisting of 17 statements regarding knowledge about the management of hypertensive crisis emergencies at home. The results of the study The level of family knowledge about the management of hypertensive crisis emergencies at home is classified as good (80%), with a small proportion classified as sufficient (16.4%) and deficient (3.6%). Conclusion: Sekarsuli Village showed that the majority of families' knowledge level about the management of hypertensive crisis emergencies at home was classified as good (80%), Keywords: Knowledge, Family, Hypertension Crisis